Analysis of mechanical engineering students' errors in solving calculus problems on function derivatives - Nina Faoziyah; Didi Kusaeri (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
Understanding calculus concepts, especially derivatives, is very important for Mechanical Engineering students to apply mathematical principles in an engineering context. This study aims to analyze the types of errors made by students when solving derivative problems and the factors that influence these errors. The approach used is descriptive qualitative with 30 students of the Mechanical Engineering Study Program at Tegal Muhammadiyah University in the 2025/2026 academic year. Data were collected through written tests and interviews, then analyzed using triangulation to ensure validity. The results of the study show that there are three main categories of errors: conceptual, procedural, and technical. Conceptual errors occurred due to a weak understanding of derivative principles. Procedural errors arose when students understood the concept but made mistakes in symbolic manipulation, while technical errors stemmed from mechanical errors, such as copying questions or incorrect arithmetic calculations. Learning strategies that emphasize conceptual understanding and gradual practice can help reduce student errors.